2019
DOI: 10.1016/j.chembiol.2018.12.001
|View full text |Cite
|
Sign up to set email alerts
|

A Soluble Metabolon Synthesizes the Isoprenoid Lipid Ubiquinone

Abstract: Highlights d Seven Ubi proteins form a 1-MDa soluble Ubi complex in Escherichia coli d The Ubi complex is a stable metabolon that catalyzes six sequential reactions d Ubiquinone, an extremely hydrophobic molecule, is synthesized in the soluble fraction d The SCP2 domain of UbiJ binds ubiquinone intermediates inside the Ubi complex

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
69
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6
2

Relationship

3
5

Authors

Journals

citations
Cited by 49 publications
(71 citation statements)
references
References 68 publications
2
69
0
Order By: Relevance
“…S2). Recently, we reported that UbiJ binds UQ biosynthetic intermediates in its SCP2 domain and organizes a multiprotein complex composed of several Ubi enzymes (16). We propose that UbiT and its SCP2 domain fulfill similar functions in the O 2 -independent UQ pathway, as UbiJ is required exclusively for the O 2 -dependent biosynthesis of UQ (Fig.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…S2). Recently, we reported that UbiJ binds UQ biosynthetic intermediates in its SCP2 domain and organizes a multiprotein complex composed of several Ubi enzymes (16). We propose that UbiT and its SCP2 domain fulfill similar functions in the O 2 -independent UQ pathway, as UbiJ is required exclusively for the O 2 -dependent biosynthesis of UQ (Fig.…”
Section: Resultsmentioning
confidence: 99%
“…In addition to the enzymes that catalyze the various steps, three accessory factors, UbiB, UbiJ, and UbiK, are also needed. UbiB has an ATPase activity (13), and we showed that UbiJ and UbiK (14, 15) belong to a multiprotein UQ biosynthesis complex, in which the SCP2 domain (sterol carrier protein 2) of UbiJ binds the hydrophobic UQ biosynthetic intermediates (16). This UQ biosynthetic pathway is dependent upon O 2 , since all three hydroxylases, UbiI, UbiH, and UbiF, use O 2 as a cosubstrate (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…We have recently demonstrated that isoprenoid quinones were able to co-elute with the Ubi-proteins such as UbiJ (11) and that UbiT exhibits a sterol carrier protein 2 (SCP2) domain (9). In this direction, we performed lipid content analysis of the UbiTPa, UbiUPa and UbiVPa fractions purified from E. coli extracts.…”
Section: Heterologously Overproduced Ubiupa and Ubitpa Co-purify Withmentioning
confidence: 99%
“…The typical UQ biosynthesis pathway requires O2 for three hydroxylation steps (10). Obviously, the flavin-dependent monooxygenases UbiI, UbiF, and UbiH, which catalyze the O2-dependent hydroxylation steps are not involved in the anaerobic pathway, nor are the accessory UbiK and UbiJ proteins implicated in the assembly and/or stability of the aerobic Ubi complex (11). The enzymes, catalyzing the prenylation, decarboxylation and methylation of the phenyl ring of the 4-hydroxybenzoate precursor, in total seven proteins (UbiA, B, C, D, E, G, X), are common to both pathways.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, knockdown of kdsC (56), encoding an enzyme involved in LPS biosynthesis, also led to sensitivity to LL37. Knockdown strains for rpoE, the gene encoding the envelope stress responsive sigma factor σ E (39,42,43), and the ubiquinone biosynthesis gene ubiJ (58) were sensitive to CSA13, but not to CSA131, also supporting the idea that these ceragenins have distinctive mechanisms of action. On the other hand, the knockdown strain for the fatty acid biosynthesis gene fabI (52,53) was sensitive to both CSA13 and CSA131 and not to the CAMPs, and may constitute a common molecular determinant of sensitivity to ceragenins.…”
Section: Identification Of Genetic Determinantsmentioning
confidence: 77%